Perencanaan Pembangunan Ekonomi Wilayah Berbasis Sektor Unggulan, Kasus : Kabupaten Pasaman Pasca Otonomi Daerah - Wenny Widya Wahyudi; Dominicus Savio Priyarsono; Amzul Rifin (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2014)
In the economic aspect, regional development planning is how to determine role of economic sector in achieving targeted growth followed by investment activity from government and private sector. Local government have limited resources and funding sources, thus the local government needs a development priority. The aims of this study are to determine the basic sector in Pasaman, to assess the budget performance of Pasaman Regency from 2004 to 2012, to analyze impact of local government budgets on the basic sector, and to determine the appropriate budget policies to increase basic sector performance. The data is analyzed with LQ (Location Quotient), SSA (Shift Share Analysis), descriptive analysis, and correlation analysis. The results showed that agriculture is a basic sector with high competitiveness than any other sector in Pasaman Regency and Pasaman Regency highly depends on the central government budget. Agriculture Gross Regional Domestic Product is highly correlated with regular budget and development budget. In order to boost performance of the agricultural sector, local government should manage its local budget strategy. The local goverment needs to increase the independence of the local budget as well as to manage its natural resources and human resources. The government also should increase the proportion of development spending, especially development budget in agricultural sector.